The effects of mobile money transfer services on traditional banking services offered by banks: case study of BancABC - Munalye, Cinderella (Midlands State University, 2017)
The Zimbabwean banking sector has experienced turbulent times resulting in the closure of many commercial banks due to liquidity problems or shortages which has also had its repercussions, as many people lost faith in the formal banking sector due to such uncertainty and perceived risks. The main aim of this research study was to investigate the effects of mobile money transfer services on traditional banking services offered by banks. A case of BancABC. The objectives of this study are; to establish the effects of mobile money transfer services on traditional banking services, secondly to establish the opportunities brought about as a result of various mobile money transfer services to BancABC and lastly to establish the challenges BancABC are facing as a result of various mobile money transfer services. Several studies pertaining the area under study have been done in the past years by many authors and scholars in other parts of the world, but a study, particularly on the effects of mobile money transfer services on traditional banking services offered by banks have not been well documented in Zimbabwe as many researchers have primarily focused on other issues such as the impact of mobile banking on financial inclusion. The insights and views of these different authorities were of significant help in the completion of this research study, as the researcher managed to identify knowledge gaps and loopholes using the ideas and suggestions by other authors, which gave the researcher a deeper astute of the proliferation and roll-out of mobile money transfer services and the effects it has on the traditional banking services offered by banks. For this particular study, the researcher adopted both exploratory and descriptive research design, using non-probability and probability sampling techniques. Questionnaires were used to collect data from the employees and one-on-one interviews were conducted in order to gather data from management personnel. The total population used for this study was 40, comprising of BancABC management and employees only. The sample size was 36. Pilot testing was done, data was gathered through the use of interviews that were conducted with management and questionnaires were distributed by the researcher to the employees. The researcher encountered some challenges in obtaining information from management and employees due to their busy and tight schedules. The researcher booked appointments to interview the managers in due time though this proved difficult they eventually squeezed in time to offer the researcher valuable information pertaining the area under study. Some respondents were also reluctant to participate as they did not want their confidentiality compromised, in order to eliminate these perceptions, the researcher assured the respondents that any information that they give will be strictly held in confidence. The data from the research study was then presented in tables, graphs and charts. The researcher recommends that BancABC should develop growth strategies along the mobile money transfer services in order to ensure growth and survival as only the survival of the fittest survive in this ever dynamic environment.